Mechanisms of host-bacterial interactions during Escherichia coli or Staphylococcus aureus infection of mammary epithelial cells - Zhao, Zhengge; Hou, Zhiming; Chai, Jianmin; Li, Chunfang; Liu, Tingyu; Li, Jianming; Zhang, Shuyi; Zhang, Lei; Ma, Yabin (Frontiers in Veterinary Science, 2025)
IntroductionMastitis is one of the costliest diseases in the dairy industry. Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) are the two most predominant pathogens. However, the specific molecular mechanisms underlying the interactions between these pathogens and bovine mammary epithelial cells, especially for two pathogenic co-infections, remain poorly understood.MethodsHere, this study employed high-throughput RNA sequencing to comprehensively analyze the gene expression changes in bovine mammary epithelial cells upon individual and co-infection with E. coli and S. aureus.ResultsTranscriptomic analysis identified 282 differentially expressed genes (DEGs) in the E. coli-infected group (E group), with 246 upregulated and 36 downregulated genes. Notably, pro-inflammatory genes (CXCL8, GRO1, CCL20) were significantly induced, and functional enrichment analysis demonstrated robust activation of inflammatory pathways including TLR/NF-κB and IL-17 signaling cascades. In contrast, the S. aureus-infected group (S group) exhibited 354 DEGs (314 upregulated, 40 downregulated), featuring pathogen-specific upregulated genes (ESM1, IL18RAP). Functional annotation revealed predominant involvement of metabolic processes, particularly ATP metabolism and chaperone complex activities. The co-infection group (ES group) displayed 307 DEGs (277 upregulated, 30 downregulated), demonstrating a unique “inflammatory-metabolic” dual-mode signature that integrated inflammatory features from the E group with metabolic reprogramming characteristics of the S group. Protein-protein interaction network analysis further delineated pathogen-specific hubs: inflammatory mediators (CXCL8, CCL20, IL6) in the E group, molecular chaperones (CCT5, RUVBL1/2) in the S group, and a distinctive IL6-FBL-centered network in co-infection. These findings elucidate pathogen-specific molecular mechanisms at the transcriptomic level, particularly revealing a unique “inflammatory-metabolic” dual-mode regulatory network during co-infection states. These findings provide new insights into the pathogenesis of mastitis and provide a theoretical basis for developing targeted prevention and control strategies.